Production of Eukaryotic Glycoproteins for Structural and Functional Studies Using Expi293F Cells. Issue 8 (23rd August 2022) - Greven, Jessica A.; Brett, Tom J.
Abstract: Milligram quantities of pure proteins are required for structural, functional, and pharmaceutical screening studies. These requirements can be challenging for a majority of important therapeutic targets that are secreted glycoproteins, receptors, membrane proteins, or large cytosolic complexes. Here, we present protocols for producing and purifying large amounts of secreted glycoproteins using the mammalian cell‐based Expi293F system via large‐scale transient transfection. This system can be easily adapted for the production of membrane proteins and large cytosolic complexes. The method can be utilized to quickly evaluate numerous expression constructs to identify optimal expressers. Use of mammalian cells ensures proper post‐translational modifications, including disulfide bonds and glycosylation, that can be important for accurate functional studies. In addition, minor modifications can be introduced to produce labeled or deglycosylated proteins for structural studies by X‐ray crystallography, nuclear magnetic resonance, or cryo‐electron microscopy. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Production of milligram quantities of plasmid DNA for large‐scale transient transfection Basic Protocol 2 : Large‐scale culture and transient transfection of Expi293F cells Basic Protocol 3 : Purification of hexahistidine‐tagged proteins from medium